Exploring the wound-healing potential and seasonal chemical variability of the Formosan Callery pear Pyrus calleryana: implications for therapeutic applications - Bo-Rong Peng; Xin-Yun Tang; Yun-Shiuan Chen; Kuei-Hung Lai; Mei-Hsien Lee (Pharmaceutical Biology)
Context Pyrus calleryana Decne (Rosaceae), renowned for its therapeutic properties, is known to moisturize the lungs (removing dryness; relieving cough), clear heat (acting as an antipyretic; febrifuge) and aid in detoxification (relieving pyogenic inflammation; eliminating toxins). However, scientific evidence supporting its efficacy in wound healing is lacking.Objective This study investigated P. calleryana samples collected over a year to explore metabolite variations and their impact on skin wound-healing activities.Materials and methods P. calleryana (PC) twigs and leaves were collected from the Matsu Islands, Taiwan, spanning 2018–2020. Extracts were prepared using 95% ethanol or water, and we assessed the chemical composition, total phenolic/triterpenoid contents and antioxidant properties. Metabolites were analysed via LC–MS/MS and molecular networking. Wound healing potential was evaluated on WS-1 cells through MTT and migration assays, and gene expression analyses, with tests including control (DMSO), compounds 1 (3′-hydroxylbenzyl-4-hydroxybenzoate-4′-O-β-glucopyranoside) and 2 (vanilloylcalleryanin) (100 µM), and a positive control (ascorbic acid, 100 µM) for 24 h.Results Significant variations in extract compositions were observed based on the solvent used, with distinct metabolomic profiles in extracts collected during different months. Notably, compounds 1 and 2 showed no cytotoxic effects on human dermal fibroblast cells and significantly accelerated wound closure at 100 μM. A gene expression analysis indicated upregulation of wound healing-associated genes, including MMP-1 (matrix metalloproteinase-1) and COL1A1 (collagen, type 1, alpha 1).Conclusions This study reports the first evidence of PC compounds aiding wound healing. Utilizing Global Natural Products Social Molecular Networking (GNPS) and principal component analysis (PCA) approaches, we unveiled metabolomic profiles, suggesting the potential to expedite wound-healing.